Physcomitrella patens as a model for studies on plant-pathogen interactions - Lehtonen, Mikko (Dissertationes Biocentri Viikki Universitatis Helsingiensis, ISSN 1799-7372, 2013)
Tiivistelmä suomeksi.
Keywords: kasvitiede; kasvipatologia; nuppusammal; sammalet; sienet; kasvitaudit; taudinaiheuttajat